2016
DOI: 10.1158/2159-8290.cd-16-0100
|View full text |Cite
|
Sign up to set email alerts
|

B Cells Promote Pancreatic Tumorigenesis

Abstract: Summary: Three recent studies, approaching the question from different angles and using different and/or overlapping models, provide compelling evidence for the involvement of tumor-infi ltrating B cells in the initiation and progression of pancreatic ductal adenocarcinoma. These studies highlight the need for a better understanding of pancreatic tumor-immune system interactions and the immunologic mechanisms that promote or inhibit tumorigenesis, paving the way for better treatment strategies. Cancer Discov; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 10 publications
(5 reference statements)
1
36
0
Order By: Relevance
“…For instance, exosomes could promote the expansion of immunosuppressive B-cell populations. Multiple studies have demonstrated that tumor-infiltrating lymphocytic B cells enhanced tumor progression through a subset of B cells with immunosuppressive functions 29,30 . Moreover, we observed that PDAC exosomes by exposing several TAAs exert a broad decoy-like function by binding circulating autoantibodies present in PDAC patient serum, thereby inhibiting complement-dependent cytotoxicity and potentially antibody-dependent cell-mediated cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, exosomes could promote the expansion of immunosuppressive B-cell populations. Multiple studies have demonstrated that tumor-infiltrating lymphocytic B cells enhanced tumor progression through a subset of B cells with immunosuppressive functions 29,30 . Moreover, we observed that PDAC exosomes by exposing several TAAs exert a broad decoy-like function by binding circulating autoantibodies present in PDAC patient serum, thereby inhibiting complement-dependent cytotoxicity and potentially antibody-dependent cell-mediated cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…B cells are known to infiltrate tumor cells during PDAC progression and support the growth of cancer cells by suppressing CD8 + T cells and tumor-associated macrophages (TAMs). Likewise, inhibition or genetic deletion of B cells leads to the activation of CD8 + T cells that further inhibit tumor cell growth (Roghanian et al, 2016 ). A study conducted in a mouse model of PDAC showed that the stroma in PanIN lesions secretes the chemokine ligand 13 (CXCL13), a chemokine that attracts B cells to the tumor periphery.…”
Section: Role Of Pi3k Signaling In the Pancreatic Tumor Microenvironmmentioning
confidence: 99%
“…Kras mutations are the earliest genetic drivers in human pancreas neoplasia, present in both early-and late-stage PanINs. Early Kras-mutated neoplastic cells secrete cytokines (e.g., IL-6), VEGF, and GM-CSF, which recruit Tregs, myeloid-derived suppressor cells (MDSCs), adipocytes and neutrophils, macrophage PI3Kγ, and chemokines (e.g., CXCL13), which recruit B-cells leading to a progressively immunosuppressive TME and immune escape (42,62,63). Kras-p53-Cre pancreatic GEMM were immunized with a Listeria vector encoded with the Kras G12D mutation and were found to generate CD8 + T-cells specific for the Kras mutation (64).…”
Section: Harnessing the Immune System For Cancer Preventionmentioning
confidence: 99%